Motif Partisipasi Politik Masyarakat Pesisir di Pemilihan Wali Kota Makassar: Studi Kasus di Kecamatan Sangkarrang Tahun 2020 - Mardaya, Andi; Muhammad, Rahmat; Abdullah, Suparman; Rais, Lukman; Wahid, Bustamin (Universitas Muhammadiyah Sorong, 2023)
This research aims to analyze the motives of political participation among coastal communities in the 2020 Makassar Mayoral Election, particularly in the Sangkarrang Islands Subdistrict. The research method employed is qualitative with a descriptive type. The informant selection technique used is nonprobability sampling with purposive sampling, where 6 informants were chosen based on specific criteria and their ability to answer research questions. The research findings indicate that political participation motives can be categorized into several factors, including intentionality, emotional factors, internal factors, external factors, and rational considerations. Intentionality arises from the understanding and awareness of individuals regarding the contribution they can make to the general election process. Meanwhile, emotional factors are related to personal relationships or shared identity, and in some situations, participation can be influenced by ethnic similarities and identity without coercion. Some individuals also engage in the election process due to emotional involvement with specific candidates. Motives for participation can also stem from social needs for communal leadership and external influences, such as political education organized by election organizers